Membrane protease prostasin promotes insulin secretion by regulating the epidermal growth factor receptor pathway - Ishii, Toshihisa; Miyasato, Yoshikazu; Ichijo, Masashi; Uchimura, Kohei; Furuya, Fumihiko (Scientific reports, 2023)
Prostasin (PRSS8) is a serine protease that metabolizes and moderates the effect of specific substrates. Epidermal growth factor receptor (EGFR), which modulates insulin secretion and pancreatic β-cell proliferation, is regulated via proteolytic shedding by PRSS8. We first detected PRSS8 expression in β-cells of pancreatic islets of mice. To better understand the molecular processes involved in PRSS8-associated insulin secretion, pancreatic β-cell-specific PRSS8 knockout (βKO) and PRSS8-overexpressing (βTG) male mice were generated. We found that glucose intolerance and reduction in glucose-stimulated insulin secretion developed in βKO mice compared with the control subjects. A higher response to glucose was noted in islets retrieved from βTG mice. Erlotinib, a specific blocker of EGFR, blocks EGF- and glucose-stimulated secretion of insulin among MIN6 cells, and glucose improves EGF release from β-cells. After silencing PRSS8 in MIN6 cells, glucose-stimulated insulin secretion decreased, and EGFR signaling was impaired. Conversely, overexpression of PRSS8 in MIN6 cells induced higher concentrations of both basal and glucose-stimulated insulin secretion and increased phospho-EGFR concentrations. Furthermore, short-term exposure to glucose improved the concentration of endogenous PRSS8 in MIN6 cells through inhibition of intracellular degradation. These findings suggest that PRSS8 is involved in glucose-dependent physiological regulation of insulin secretion via the EGF–EGFR signaling pathway in pancreatic β-cells.